Ownership, technological capabilities and exports of garment firms in Myanmar - Rasiah, Rajah; Myint, Myo Myo (Technological and Economic Development of Economy, 2014)
This paper uses the evolutionary framework to examine the relationship between ownership, technological capabilities and export intensities using garment manufacturing in the Least Developed Country of Myanmar as an empirical case. The results show that foreign firms with production connected to global value chains enjoy higher export intensity than national firms even when controlled for age. Also, foreign firms with access to superior support from parent plants enjoy higher technology capability than national firms even after controlling for age. The Levene’s two-tail ‘t’ tests show that foreign firms also enjoyed higher human resource, process technology and adaptive capabilities than national firms. Foreign firms are also larger and pay higher wages than national firms. The results show that foreign firms’ superior market access and technological capabilities can offer the potential for knowledge spillover to national firms provided the government stabilizes the political situation and strengthens the basic and high technology infrastructure in Myanmar. Unlike the Maquiladoras of Latin America, not only that a quarter of the inputs are sourced by garment firms from Myanmar, a handful of national firms have already acquired the export and technological capabilities to compete with foreign firms.